Pemanfaatan Media Sosial Tiktok dalam Upaya Pelestarian Tari Topeng Cirebon Sebagai Respons Generasi Z untuk Mempertahankan Identitas Bangsa - Susilo, Jimat; Olivia, Olivia; Karimah, Siti; Salsabilah, Anggita; Al Farizi, Vionny; Kurniasih, Nita (Sosio-Didaktika: Social Science Education Journal, 2024)
In the current digital era, technological advancements play a crucial role in addressing the challenges faced by society, particularly for Generation Z, who prioritize convenience and speed in communication. Social media platforms, especially TikTok, have become effective tools for promoting and preserving local cultures, including the Mask Dance from Cirebon. This research aims to assess the effectiveness of TikTok as a means of preserving the Topeng Mask Dance among Generation Z. The study employs a qualitative approach, utilizing data collection methods such as documentation, observation, and interviews. Data analysis is performed through content analysis, examining Generation Z's responses to the Topeng Mask Dance on TikTok. The findings indicate that TikTok is highly effective in increasing the visibility and recognition of the Topeng Mask Dance among Generation Z. The interactions reveal positive engagement from users who show a high level of interest in informative content. This research recommends collaborating with dance experts to develop creative ideas through digital platforms to ensure the continued preservation of cultural heritage. Therefore, TikTok serves not only as a source of entertainment but also as a vital tool for preserving and introducing local culture to the younger generation, thereby strengthening national identity amid globalization.